2015
DOI: 10.1086/681108
|View full text |Cite
|
Sign up to set email alerts
|

State Merit Aid Programs and College Major: A Focus on STEM

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 54 publications
4
39
0
Order By: Relevance
“…Policies that encourage historically underrepresented groups to major in STEM fields may be able to increase the stock of STEM graduates and serve other social goals. Finally, there is evidence that some potential STEM students respond to incentives provided by financial aid programs (Denning and Turley 2013;Sjoquist and Winters 2013). Scholarship programs specifically targeted to STEM fields may be able to increase STEM education for students at the margin of majoring in STEM or not.…”
Section: Resultsmentioning
confidence: 99%
“…Policies that encourage historically underrepresented groups to major in STEM fields may be able to increase the stock of STEM graduates and serve other social goals. Finally, there is evidence that some potential STEM students respond to incentives provided by financial aid programs (Denning and Turley 2013;Sjoquist and Winters 2013). Scholarship programs specifically targeted to STEM fields may be able to increase STEM education for students at the margin of majoring in STEM or not.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Castleman and Long (2013) and Sjoquist and Winters (2014a) find that aid had no impact on students earning an associate's degree by studying FSAG eligibility and the Georgia HOPE scholarship, respectively. Other studies have also considered whether merit aid programs affect major choice and have found that students are less likely to pursue majors in science, technology, engineering, and math (STEM) fields due to the introduction of merit aid programs (Cornwell, Lee, & Mustard, 2006;Sjoquist & Winters, 2014b). While some of these studies do include community college students and four-year students in their sample, none have yet focused exclusively on community college students or examined post-college earnings.…”
Section: Related Literaturementioning
confidence: 99%
“…They find that students responded to the reduction in debt by choosing lower‐salary jobs, although they do not find an effect on the choice of major or on academic performance. In two related studies, Sjoquist and Winters (,b) look at the effect of financial aid on the probability of graduating from a STEM subject. They use variation in financial aid across US states, and find that the adoption of a strong aid programme had a negative effect on the number of STEM graduates.…”
Section: Introductionmentioning
confidence: 99%